Ligand cleavage put into reverse: P-C bond breaking and remaking in an alkylphosphane iron complex - Heinemann, Frank Wilhelm; et al. (Chemistry - A European Journal, 2006)
Complex formation between FeX(2)(.)6H(2)O (X=BF4 or ClO4) and the pyridine-derived tetrapodal tetraphosphane C5H3N[CMe(CH2PMe2)(2)](2) (1) in methanol proceeds with solvent-induced cleavage of one PMe2 group. Depending on the reaction temperature and the nature of the counterion, iron(II) is coordinated, in distorted square-pyramidal fashion, by the anionic remainder of the chelating ligand, C5H3N[CMe(CH2PMe2)(2)][CMe(CH2PMe2)(CH2-)] (Np3C- donor set: X = BF4, -50 degrees C: 2; X = ClO4, RT: 4) or its protonated form C5H3N[CMe(CH2PMe2)(2)][CMe(CH2PMe2)(CH3)], in which the methyl group is in agostic interaction with the metal centre (X=BF, RT: 3; X=ClO4, +50 degrees C: 5). A monodentate phosphinite ligand Me2POMe, formed from the cleaved PMe2 group and methanol, completes the coordination octahedron in both cases. Working in CD3OD (X=BF4, RT) gives the deuterium-substituted analogue of 3, with ligands L(CH2D) (L=residual chelating ligand) and Me2POCD3. A mechanism for the observed phosphorus-carbon bond cleavage is suggested. Complex 2, when isolated at -50 degrees C, is stable in the solid state even at room temperature. The reaction of 2 in methanol with carbon monoxide (10.5 bar) at elevated temperature forms, in addition to as yet unidentified side products, the carbonyl complex [(1)Fe(CO)](BF4)(2) (7), in which the previous P-C bond cleavage has been reversed, reforming the original tetrapodal pentadentate NP4 ligand 1. All compounds have been fully characterised, including X-ray structure analyses in most cases.
Keywords: agostic interactions; iron; N; P ligands; P-C activation; tetrapodal ligands